Nurses Self-Efficacy Caring for COVID-19 Patients: A Qualitative Study - Rai Dewi Damayanthi Pande; Dinar Saurmauli Lubis; Cokorda Bagus Jaya Lesmana (Nursing and Health Sciences Journal (NHSJ), 2023)
The Covid-19 pandemic causes nurses to experience various physical and mental stresses to deal with rapid case escalation with severe patient conditions. The workload of nurses is increasing and they are required to quickly adapt to the change in the function of the treatment room into a Covid-19 Isolation Room. High self-efficacy is needed for motivation and performance as well as controlling stress. This study aims to obtain an overview of the sources of nurse self-efficacy and explore other themes related to nurse self-efficacy in the Covid-19 Isolation Room. This research is a qualitative research by conducting semi-structured in-depth interviews with 12 informants. The informants were selected by purposive sampling consisting of the shift nurse, the team leader and the head nurse. Data analysis techniques with manual thematic analysis. The stress faced by nurses in the Covid-19 Isolation Room is related to workload, job risks and relational relationships at work and in the community. Sources of informants' self-efficacy were obtained from mastery experiences through internships, vicarious experiences from role models and social persuasion from friends and superiors. Three themes were found that affect self-efficacy, namely personal, organizational and external variables. In each theme also found several sub-themes. In order to increase nurse's self-efficacy, it is necessary to utilize self-efficacy sources, maximize personal variables and get support from family and organizations.